Assessing urogenital schistosomiasis and female genital schistosomiasis (FGS) among adolescents in Anaocha, Anambra State, Nigeria: implications for ongoing control efforts - Ogechukwu B. Aribodor; Nwadiuto O. Azugo; Eunice C. Jacob; Uche C. Ngenegbo; Nnaemeka D. Onwusulu; Ifeanyi Obika; Emmanuel M. Obikwelu; Obiageli J. Nebe (BMC, 2024)
Abstract Background Urogenital schistosomiasis (UgS) remains a persistent health challenge among adolescents in Anambra State, Nigeria, despite ongoing control efforts. Mass praziquantel treatment programs, initiated in 2013, primarily target primary school-aged children (5-14 years old), leaving adolescents (10-19 years old) enrolled in secondary schools vulnerable to urogenital schistosomiaisis. Additionally, the extent of female genital schistosomiasis (FGS), a neglected gynaecological manifestation of UgS remains unclear. Methodology To address these gaps, a cross-sectional study was conducted in Anaocha Local Government Area from February to May 2023. Four hundred and seventy consenting adolescents aged 10-19 years were enrolled. Urinalysis including urine filtration was employed to confirm haematuria and detect urogenital schistosomiasis (UGS) among the participants. For females with heavy infections (≥ 50 eggs/10 ml urine), a gynaecologist performed colposcopy examinations, complemented by acetic acid and Lugol's iodine staining to assess for female genital schistosomiasis (FGS) lesions or other related reproductive health conditions. Socio-demographic data, including information on potential risk factors, were systematically collected using the Kobo ToolBox software, following gender-sensitive data collection guidelines. Data were analysed using SPSS version 25, incorporating descriptive statistics, multinomial logistic regression, odds ratios, and significance testing. Results Among the 470 adolescents (52.8% females, 47.2% males) examined, an overall UgS prevalence of 14.5% was observed, with an average of 5.25 eggs per 10 ml of urine. Females had a slightly higher prevalence (16.1%), and 7.5% had heavy infections. Although gender differences in infection rates were not statistically significant, males had slightly higher odds of infection (OR: 1.332; 95% CI: 0.791-2.244; p-value: 0.280). Adolescents aged 10-14 had the highest prevalence, with significantly increased odds of infection (OR: 1.720; 95% CI: 1.012-2.923; p-value: 0.045). Colposcopy examinations of females with heavy infections revealed FGS lesions and co-infections with Trichomonas vaginalis. Haematuria, though prevalent (24.6%), was not the sole indicator, as those without it faced significantly higher odds of infection (OR: 2.924; 95% CI: 1.731-4.941; p-value: 0.000). Dysuria and genital itching/burning sensation were other UgS and FGS associated symptoms. Direct water contact was associated with higher infection odds (OR: 2.601; 95% CI: 1.007-6.716; p-value: 0.048). Various risk factors were associated with UgS. Conclusion The study highlights the need for a comprehensive Urogenital Schistosomiasis (UGS) control strategy that includes secondary school adolescents, emphasizes risk factor management, promotes safe water practices, and raises awareness about UGS and Female Genital Schistosomiasis (FGS) among adolescents, thus improving control efforts and mitigating this health challenge in the region.